2017
DOI: 10.1038/s41598-017-11060-z
|View full text |Cite
|
Sign up to set email alerts
|

Light rare earth element depletion during Deepwater Horizon blowout methanotrophy

Abstract: Rare earth elements have generally not been thought to have a biological role. However, recent work has demonstrated that the light REEs (LREEs: La, Ce, Pr, and Nd) are essential for at least some methanotrophs, being co-factors in the XoxF type of methanol dehydrogenase (MDH). We show here that dissolved LREEs were significantly removed in a submerged plume of methane-rich water during the Deepwater Horizon (DWH) well blowout. Furthermore, incubation experiments conducted with naturally methane-enriched water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 68 publications
2
38
0
3
Order By: Relevance
“…These observations support the assumption that ε Nd is conservative or "quasi-conservative" in the oceans and will trace water masses in a manner similar to temperature and salinity (Frank, 2002;Goldstein and Hemming, 2003). Furthermore, elemental Nd is assumed to have negligible bioactivity, although recent work suggests that there are important caveats to this assumption (Shiller et al, 2017). However, because of the concerted efforts invested into measuring neodymium in the oceans as well as within sedimentary archives, inconsistencies between the observed distributions and the assumptions inherent in the use of the Nd as a tracer are becoming increasingly apparent.…”
Section: Introductionsupporting
confidence: 53%
“…These observations support the assumption that ε Nd is conservative or "quasi-conservative" in the oceans and will trace water masses in a manner similar to temperature and salinity (Frank, 2002;Goldstein and Hemming, 2003). Furthermore, elemental Nd is assumed to have negligible bioactivity, although recent work suggests that there are important caveats to this assumption (Shiller et al, 2017). However, because of the concerted efforts invested into measuring neodymium in the oceans as well as within sedimentary archives, inconsistencies between the observed distributions and the assumptions inherent in the use of the Nd as a tracer are becoming increasingly apparent.…”
Section: Introductionsupporting
confidence: 53%
“…Moreover, Shiller et al . () observed preferred and active uptake of the LREEs by aerobic methanotrophs from the water column in response to the Deepwater Horizon oil spill (Gulf of Mexico), further suggesting that LREE enrichment may be related to the metabolism of oil‐consuming microbial communities or be related to the oil itself.…”
Section: Discussionmentioning
confidence: 99%
“…Finely crystalline grey aragonite in the present study represents a modern equivalent of yellow aragonite and calcite, which have been identified in numerous Phanerozoic methaneseep deposits (Zwicker et al, 2018, and references therein). Moreover, Shiller et al (2017) observed preferred and active uptake of the LREEs by aerobic methanotrophs from the water column in response to the Deepwater Horizon oil spill (Gulf of Mexico), further suggesting that LREE enrichment may be related to the metabolism of oil-consuming microbial communities or be related to the oil itself.…”
Section: Geochemical Modellingmentioning
confidence: 98%
“…The plumes in the ocean led to a bloom of methanotrophic bacteria, and a recent study showed that, concurrently with methane consumption, a depletion of light rare earth elements (REEs: La, Ce, Pr, and Nd) from the surrounding seawater was observed . This phenomenon can be explained in terms of the biological role of REEs for methanotrophic and methylotrophic bacteria . These bacteria utilize C1 compounds, such as methane and methanol, as an energy source.…”
Section: Introductionmentioning
confidence: 99%